Radioiodine sorbent selection criteria - Riley, Brian J.; Carlson, Krista (Frontiers in Chemistry, 2022)
Methods for preventing radioiodine from entering the environment are needed in processes related to nuclear energy and medical isotope production. The development and performance of many different types of sorbents to capture iodine have been reported on over decades; however, there is yet to be a report on the important parameters that should be considered when selecting a material for chemically capturing radioiodine. This paper summarizes several criteria that should be considered when selecting candidate sorbents for implementation into real-world systems. The list of selection criteria discussed are (1) optimal capture performance, (2) kinetics of adsorption, (3) performance under relevant process conditions, (4) properties of the substrate that supports the getter, and (5) stability of the iodine-loaded materials formed after capture and disposition pathways.